Participation, Persistence, and Attainment Rates: The US Standing - Hauptman, Arthur M. (International Higher Education, 2008)
Several recent reports in the United States have compared the American performance in higher education to that of other Organization for Economic Cooperation and Development (OECD) countries, and concern that the United States is slipping when it comes to attainment rates in tertiary education. However, the United States continues to have among the highest participation rates among OECD countries, below average rates of completion, among the highest attainment rates for bachelor's degrees, and average to below average attainment rates for subbachelor's degrees. One key conclusion from this analysis is that a key challenge for the United States is to figure out how to improve the degree completion rate of its community college students.